Being Leftist and Jewish in Greece during the Civil War and its Aftermath: Constraints and Choices - Beze, Eleni (Historein, 2019)
After the end of the Second World War, and as a result of the ensuing Greek Civil War (1946–1949), former resistance members went through a period of generalised, severe persecution. In this context, Jews who had survived the Shoah by taking part in the resistance in some way or by going into hiding under the protection of the resistance forces had to denounce their former comrades or communist rescuers. How did Greek Jews who had been influenced by leftist ideology respond to the politics of the civil war and its aftermath? How were their responses affected by the attitudes of the Greek state, Jewish community and State of Israel towards them? Following the traces left mainly in a) the archives of the Jewish Museum of Greece, the Jewish communities of Athens and Salonica, and the American Jewish Joint Distribution Committee; b) the Greek Jewish press of the period; c) personal accounts, essays and literature, I will attempt to explore the multiplicity of responses of leftist Greek Jews to the political and personal dilemmas of the post-Shoah period. I argue that despite different postwar (and prewar) political attitudes and experiences, leftist Greek Jews expressed two main tendencies: a tight relationship with the country’s Jewish communities and, at the same time, a strong tendency to leave for other countries, mainly Israel.